The Application of Virtual Instrument Technology in the Tester - Jianhua Ren; Xiaogang Guo; Yanceng Liu; Li Chen (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Four-ball tester is a device which is used to evaluate the resistance of extreme pressure grease performance and wear resistance with simple structure, less fuel consumption and low cost. It has been widely used in Lubricants research. In this paper, the principle and testing equipment of four-ball tester are introduced. At the same time, some shortcomings such as inconvenient load mechanism and inaccurate measurements are presented. Friction testing and recording system is improved on the basic of the previous system to avoid the defects. Amplification ratio of the friction test result increases significantly.  To improve precision and convenience for data storing, analysis and comparison, data acquisition system is established based on LabVIEW. Then friction measurement process is visualization to realize the measured results being observed visually. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3103